Methods of Teaching Law as a Science: Research Methods, Categorial-Conceptual Apparatus, Condition of Scientific and Educational Literature - Lilya Riabovol (Pedagogical Discourse, 2017)
In the article the author presents the results and conclusions of the study on the essence and specifics methods of teaching law (jurisprudential didactics). The attention to these mandatory attributes of this science, as research methods, categorial-conceptual apparatus, condition of scientific and educational literature. Found that for scientific research on methods of teaching law using the system of theoretical, empirical, mathematical (statistical) methods, including: analysis, synthesis, comparison, generalization, systematization, classification, system-structural analysis, modeling; diagnostic methods (observation, testing, interviewing teachers and students, the method of expert estimates ranging answers and summary results table); predicting the results of experimental work on the basis of the data received; special role played by pedagogical experiment. It was found that the methods of teaching law uses categories of general didactics, however, has developed its own conceptual apparatus that constantly improved and enriched; provides a list of relevant concepts, including: school legal education, education law, school system of legal education, training system of jurisprudence, legal substantive competence, contents school legal education, law as a subject, educational jurisprudential material, the empirical jurisprudential material, theoretical jurisprudential material, legal knowledge, legal concepts, legal thinking, law school, method of teaching law, form of education jurisprudence, interactive lesson law, methodical system of training of law-oriented development of students’ competencies. The state is elaborated scientific and educational literature (monographs, textbooks, manuals), which reflected the conclusions and results of studies conducted in this area. Expounded the author’s interpretation of such signs scientific knowledge of jurisprudential didactics, as the focus on an object, systematic, validity, targeting, relevance and importance.Key words: methods of teaching law, jurisprudential didactics, research methods, conceptual apparatus, law training, methodical system of training of law.